Responsabilidad social empresarial en el contexto del COVID-19 - Quevedo Barros, Manuel Rafael (2021)
The human tragedy and the economic, social and environmental implications of the coronavirus disease 2019 (COVID-19) caused a great impact in various economic sectors worldwide, opening the possibility of applying strategies related to Corporate Social Responsibility (CSR). Therefore, the main purpose of the article is to offer a vision on the impact of the coronavirus disease COVID-19 or SARS-CoV-2 on corporate social responsibility (CSR), in relation to the practice and generation of opportunities oriented to overcome global social and environmental challenges for the management of organizations developed in the context of the pandemic. Concluding that the joint work between the economic, social and environmental promotes the generation of benefits to companies and society, where the crisis due to the pandemic promotes a change in the vision and approach of organizations to actively participate in CSR initiatives through a short and long term.